Plastic pollution under the influence of climate change: implications for the abundance, distribution, and hazards in terrestrial and aquatic ecosystems - Kelly, Frank J.; Wright, Stephanie L.; Woodward, Guy; Fussell, Julia C. (Frontiers in Science, 2025)
Of the numerous anthropogenic pressures that are being exerted on ecosystems globally, plastic pollution and climate change are potentially the most pressing. This is particularly true when they co-occur as joint stressors. These are interlinked with respect to their root cause (the overconsumption of finite resources) and their effects in natural and anthropogenic systems and processes. This review focuses on a growing area of research into how climate change can, by transforming plastic pollution from a reversible to a poorly reversible contaminant, exacerbate the abundance, distribution, exposure, and impacts of plastics and associated chemicals in our waters, soils, biota, and atmosphere. There is a growing body of evidence suggesting that climate change and plastic pollution can have significant and often interactive ecological effects, particularly among the higher trophic levels within the food web. The rational response to confront these effects is to address the pollution at source by rapidly and meaningfully reducing emissions into the environment. We discuss challenges but also solutions, through future research, policies and public awareness, that must harness the same enthusiasm that made plastic a fundamental cornerstone of the modern world in the first place. The threat that plastics produced, used and discarded today could cause global-scale impacts in the future is compelling motivation to take appropriate action now.